2001
DOI: 10.1097/00005650-200106000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Medical Care Expenditures for Hypertension, Its Complications, and Its Comorbidities

Abstract: The economic burden of hypertension is large, but health services directly related to hypertension account for only a fraction of attributed expenditures. Comprehensive accounting of expenditures more accurately assesses the cost of hypertension and potential savings from prevention and treatment. Alteration of lifestyles and medical intervention provide opportunities to reduce national health expenditures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 33 publications
3
99
1
6
Order By: Relevance
“…Some studies have demonstrated an association between comorbidity and healthcare costs 32, 33, 34. In our study, comorbidity was found to be associated with higher pharmaceutical expenditure among people with established ASCVD.…”
Section: Discussionsupporting
confidence: 60%
“…Some studies have demonstrated an association between comorbidity and healthcare costs 32, 33, 34. In our study, comorbidity was found to be associated with higher pharmaceutical expenditure among people with established ASCVD.…”
Section: Discussionsupporting
confidence: 60%
“…Descriptions of the WHI study and additional details describing this study have been published. 9 The WHI eligibility criteria included: (1) age at entry between 50 to 79; (2) the ability and willingness to provide written informed consent for the pertinent program components; (3) an expectation of being resident in the study recruitment area for at least 3 years following enrolment; and (4) the absence of any exclusion criterion. Exclusion criteria were: (1) presence of medical conditions predictive of a survival time of o3 years; (2) conditions or characteristics inconsistent with study participation and adherence (alcoholism, drug dependency, mental illness and dementia); and (3) active participants in a randomized controlled clinical trial.…”
Section: Study Subjectsmentioning
confidence: 99%
“…11 We also used categorical classifications (hypertensive or normotensive) to assess the odds ratios (OR) for hypertension in the admixed populations. For these assessments, we used the following definitions: (1) In addition, we also performed analyses in which individuals that met either diastolic or systolic definitions were classified as hypertensive and individuals meeting both diastolic and systolic definitions for the normal range were classified as normotensive.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, si un paciente no cumple con las indicaciones médicas es imposible estimar el efecto del tratamiento, lo que a su vez puede contribuir a prolongar la terapia y perpetuar enfermedades o problemas de salud e incluso conducir a la muerte, con el consecuente costo económico para el estado, tanto en materias relativas a pérdida de productividad y costos asociados a rehabilitación y pensiones de invalidez (por ejemplo, el costo asociado al tratamiento de la hipertensión y sus complicaciones representó 12,6% del gasto total de atención de salud en Estados Unidos de Norteamérica en 1998) 7 .…”
unclassified